KONSEP BARU PENGEMBALIAN KERUGIAN NEGARA DARI TINDAK PIDANA KORUPSI - Yudi Wibowo Sukinto (Universitas Airlangga, 2016)
The new concept of returns losses state finance on corruption based on The Theory of Imprisonment for Non Payment of Fine, firstly came from Singapore state placed in the Criminal Procedure Code Singapore, and the Singapore Customs Act Chapter 70, 119, which requires the convicted person to pay losses to the state. Losses States referred to either a fine of the decision of the judge or of the money indemnity State then in that State applied The Imprisonment for Non Payment of Fine, so the convict is given a prison sentence must conform table the amount of loss Country / Region generated, the equivalent length of additional criminal the perpetrator of a crime, if it is applied in Indonesia is very effective at all, especially in the implementation of the compensation losses Country/Region due to corruption, so it will certainly bring a deterrent effect on criminals. In Indonesia, the the Parliament who make the policy of the legislature or make Act most pleased coupled with Criminal Provisions which adheres to sentencing by the deterrent effect which intends to apply the theory of retributive namely bringing the perpetrators to suffer a sentence for committing a crime, so it is no longer thinking about how to indemnification countries / areas due to a criminal act, by the offender.